Exploring succession in small business growth in Bandung: Mediating role of strategic change - Johan, Ahmad; Sriwardani, Sriwardani; Oktavian, Rizky Ferrari (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Purpose – This study aims to understand the influence of organizational agility and organizational resilience towards SMEs business performance and analyze the mediating role of strategic change and the moderating role of environmental uncertainty.Design/methodology/approach – This study uses quantitative approach with survey method. The population of the study is SMEs business actors in Bandung, West Java. The samples are chosen for about 250 respondents using purposive sampling, while the data is processed using structural equation modelling with Partial Least Square.Findings – The results indicate positive influence of organizational agility on organizational resilience, as well as organizational resilience on SMEs business growth. Additionally, strategic change is found to mediate the relationship of organizational resilience towards SMEs business growth. Environmental uncertainty can strengthen the influence of organizational resilience on strategic change.Research limitations/implications – The results of this research provide evidence that the underlying mechanisms for increasing organizational resilience and SME business growth can be seen from the perspective of organizational agility and choosing the right strategy.Practical implications – This study underscores the importance of building organizational agility and resilience to face dynamic environmental situation characterized by rapid change. When SMEs are adaptive and more responsive in carrying out their business, this can lead to positive outcomes for their growth.Originality/value – The present study provides the underlying mechanisms that shows how organizational agility and resilience can lead to SMEs business growth which operate in the uncertain environment.